Brief Communication "Expansion of meltwater lakes on the Greenland Ice Sheet" - M. R. van den Broeke; J. T. M. Lenaerts; J. H. van Angelen; S. de la Peña; I. M. Howat (The Cryosphere, 2013)
Forty years of satellite imagery reveal that meltwater lakes on the margin of the Greenland Ice Sheet have expanded substantially inland to higher elevations with warming. These lakes are important because they provide a mechanism for bringing water to the ice bed, causing sliding. Inland expansion of lakes could accelerate ice flow by bringing water to previously frozen bed, potentially increasing future rates of mass loss. Increasing lake elevations closely follow the rise of the mass balance equilibrium line over much of the ice sheet, suggesting no physical limit on lake expansion. Data are not yet available to detect a corresponding change in ice flow, and the potential effects of lake expansion on ice sheet dynamics are not included in ice sheet models.